Learning ethics through the Metaverse: challenges and responsible educational design solutions - Haugsbakken, Halvdan; Hagelia, Marianne; Bergsjø, Leonora Onarheim (Frontiers in Education, 2025)
This conceptual paper explores the potential of learning and teaching ethics in the Metaverse. This argument will be developed by exploring two different perspectives. The first perspective situates the paper within a broader context and discusses five challenges that arise from using the Metaverse. These challenges include the impact of new technologies on ethics, establishing trust in the Metaverse, accessibility to Metaverse technologies, how institutions engage in power plays to influence and set norms for ethical standards, and issues related to data ownership and intellectual property. The second perspective considers and conceptualizes four responsible educational design solutions that can be applied to facilitate learning ethics within the Metaverse. This means addressing the extent to which the Metaverse can support transformative learning, identity experimentation, immersive technology-enhanced learning, and collaborative approaches. Taken together, these perspectives provide a starting foundation and research contribution for creating an alternative pedagogical and practical framework that reconceptualizes the Metaverse as pedagogical space for reflective–practical sensemaking and exploration about ethics in education.